Pelatihan Peningkatan Kompetensi Guru TPQ di Kampung Padang Lawe Nagari Amping Parak Kecamatan Surantih - Anjeli, Mardawila Adha; Kustati, Martin; Gusmirawati, Gusmirawati (Al-DYAS, 2023)
This activity was held with the aim of providing training to increase the competency of TPQ teachers in teaching good and correct reading and writing of the Alquran. Alquran teachers or what are usually called AlquranEducation Park (TPQ) teachers, TPQ teachers essentially carry out a noble mission in maintaining the existence of the Al-Quran. For this reason, it is important for us to follow up and commit to teaching the Alquran properly and correctly to the next generation, which must be implemented as early as possible, so that the AlquranEducation Place (TPQ) becomes the focus of research and service. This activity was carried out using the Participatory Action Research (PAR) method which consists of planning, implementing, discovering facts about the results of actions, and discovering new meanings from social experiences. The targets for this training activity are TPQ teachers at the Amping Parak Surantih mosque and prayer room. The target for success of this training is that the teacher is able to pronounce the letters according to their makhraj, the teacher understands basic tajwid material, the teacher can write Arabic letters correctly. The implementation of this training received a positive response from the teachers. This research was conducted to develop an effective training program in improving the competency of TPQ teachers using the lecture method.